Trust Also Means Centering Black Women's Reproductive Health Narratives - Thomas, Shameka Poetry (The Hastings Center report, 2022)
This commentary responds to Yolonda Wilson's article "Is Trust Enough? Anti-Black Racism and the Perception of Black Vaccine ‘Hesitancy’" by connecting mistrust to the phenomenon in the United States of blaming Black women for their own adverse health outcomes, particularly in the context of maternal and reproductive health. When medical practitioners and researchers fail to recognize and understand the racist social context of health problems, Black women and other minoritized groups are socialized to mistrust their bodies; as a result, these groups can come to mistrust medical institutions, and medical institutions to distrust patients from these groups. Highlighting the disproportionately and unjustly high maternal mortality rates among Black women, this commentary warns that neglecting to center the narratives of Black women tells an incomplete story of reproductive health disparities in the United States. Drawing on firsthand experience conducting qualitative reproductive-health research with Black women, the author urges professionals in reproductive medicine and bioethics to use the tools of narrative medicine to listen to and center Black women's accounts of their lived experiences in order to deconstruct blame and work toward eliminating reproductive health disparities.